Opportunities for Innovation in Genetic Transformation of Forest Trees - Nagle, Michael; Déjardin, Annabelle; Pilate, Gilles; Strauss, Steven H. (Frontiers in Plant Science, 2018)
The incorporation of DNA into plant genomes followed by regeneration of non-chimeric stable plants (transformation) remains a major challenge for most plant species. Forest trees are particularly difficult as a result of their biochemistry, aging, desire for clonal fidelity, delayed reproduction, and high diversity. We review two complementary approaches to transformation that appear to hold promise for forest trees.